The Challenges in Teaching English Online to Young Learners: Teachers' Voices - Wensi Alka; Dzulfikri D; Khaula Amelia Khusna; Hainona Izza Golia (Universitas Nahdlatul Ulama Surabaya, 2023)
Teaching and learning activities had shifted to online classes due to Covid-19 pandemic outbreaks. Hence,primary school teachers in Indonesia encountered several challenges with the unexpected changes inEnglish face-to-face classroom interaction to online learning with digital platforms. This study exploredthe challenges faced by four Indonesian EFL primary school teachers in implementing online learningand teachers' solutions to the challenges. A qualitative study with a phenomenological approach was usedas the research design, and the data collection was obtained through observation and interview. Thisstudy showed that teachers found online English Language Teaching (ELT) activities more difficult thanface-to-face classrooms due to some challenges. The technical issue became the first challenge faced bythe teachers since both teachers and students needed an internet connection and device management.Secondly, most teachers found it difficult to implement various teaching methods in online learning. Theother reasons were that enhancing students' engagement required more effort, and assessing students'English development took more work than in the face-to-face classroom. The implication of this researchis for teachers and students as it may help them address and generate new insights about the challengesand solutions in online classrooms. Furthermore, it highlights specific areas for future research.